The roles of RgpB and Kgp in late onset gingipain activity in the vimA-defective mutant of Porphyromonas gingivalis W83 - Dou, Yuetan (Mol Oral Microbiol, 2015)
Previous studies have shown that VimA, an acetyltransferase, can modulate gingipain biogenesis in Porphyromonas gingivalis. Inactivation of the vimA gene resulted in isogenic mutants that showed a late onset of gingipain activity that only occurred during the stationary growth phase. To further elucidate the role and contribution of the gingipains in this VimA-dependent process, isogenic mutants defective in the gingipain genes in the vimA-deficient genetic background were evaluated. In contrast to the wild-type strain, RgpB and Kgp gingipain activities were absent in exponential phase in the ΔrgpA::tetQ-vimA::ermF mutant. However, these activities increased to 31% and 53%, respectively, of that of the wild-type during stationary phase. In the ΔrgpA::cat-Δkgp::tetQ-vimA::ermF mutant, the RgpB protein was observed in the extracellular fraction but no activity was present even at the stationary growth phase. There was no gingipain activity observed in the ΔrgpB::cat-Δkgp::tetQ-vimA::ermF mutant while Kgp activity in ΔrgpA::cat-ΔrgpB::tetQ-vimA::ermF mutant was 24% of the wild-type at late stationary phase. In contrast to RgpA, the glycosylation profile of the RgpB catalytic domain from both W83 and P. gingivalis FLL92 (vimA::ermF) showed similarity. Taken together, the results suggest multiple gingipain activation pathways in P. gingivalis. While the maturation pathways for RgpA and RgpB are different, the late onset gingipain activity in the vimA-defective mutant was due to activation/maturation of RgpB and Kgp. Moreover, unlike RgpA which is VimA-dependent, the maturation/activation pathways for RgpB and Kgp are interdependent in the absence VimA.